Punishing Groups: When External Justice Takes Priority over Internal Justice. (9th March 2019) - Himmelreich, Johannes; Lawford-Smith, Holly
Abstract: Punishing groups raises a difficult question, namely, how their punishment can be justified at all. Some have argued that punishing groups is morally problematic because of the effects that the punishment entails for their members. In this paper we argue against this view. We distinguish the question of internal justice—how punishment-effects are distributed—from the question of external justice—whether the punishment is justified. We argue that issues of internal justice do not in general undermine the permissibility of punishment. We also defend the permissibility of what some call "random punishment." We argue that, for some kinds of collectives, there is no general obligation to internally distribute the punishment-effects equally or in proportion to individual contribution.